The Impact of Digital Health in Healthcare Communication and Service Delivery, Rural Eastern Cape - Nomputumo Linah Ngesimani; Errol Francke (WISE Pendidikan Indonesia, 2025)
This study explores the impact of digital health in healthcare communication and service delivery in rural areas. A qualitative method was employed, and data were collected through interviews with 19 healthcare professionals (HPCs) across various roles in healthcare facilities. The data was analysed thematically using ATLAS.ti v9. The findings revealed that several digital health tools (DHTs) are currently in place, including the District Health Information System, Human Management System 2, e-Tick register, Health Patient Registration System, and Lab Trak. The findings also revealed that digital health (DH) improves data management, processing, and transmission, and minimises cost and time in rural healthcare. Additionally, social messaging platforms, such as WhatsApp, facilitate effective communication among HCPs and patients across rural facilities. Nevertheless, this study identified several challenges, including digital literacy to HCPs, age-related barriers, and a lack of personnel. Moreover, the study revealed operational challenges, including system backlogs and potential data duplication and loss, all linked to poor internet connectivity and power failures. Notably, digital health enablers (DHEs), including backup power generators, solar systems, fibre and Wi-Fi connectivity, and uninterruptible power supply, were identified as key enablers to improve the operation of digital health in rural communities. This study contributes to the understanding of context-specific insights into how DHTs are experienced and sustained in the real world. Additionally, this study identified facility-level enablers, ultimately demonstrating practical strategies that support the operation of DH in rural healthcare.